2016
DOI: 10.1539/joh.15-0056-oa
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value and construct validity of the work functioning screener‐healthcare (WFS‐H)

Abstract: Objectives: To test the predictive value and convergent construct validity of a 6-item work functioning screener (WFS-H). Methods: Healthcare workers (249 nurses) completed a questionnaire containing the work functioning screener (WFS-H) and a work functioning instrument (NWFQ) measuring the following: cognitive aspects of task execution and general incidents, avoidance behavior, conflicts and irritation with colleagues, impaired contact with patients and their family, and level of energy and motivation. Produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Furthermore, the reseach so far showed that emotional exhaustion may be a predictor of work functioning problems 3 . Furthermore, work engagement (ie, the positive work‐related psychological state of well‐being that is conceptualized by vigor, dedication and absorption 15 ), as the distinct concept that is negatively related to burnout and the predictor of well‐being and work motivation demonstrated in many studies (eg, Christian et al 16 ), was found to be only marginally related to work functioning problems by Abma and colleagues 11,12 . Accordingly, due to the mixed study findings so far it is important to conduct additional research on the predictors of the work functioning of workers.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Furthermore, the reseach so far showed that emotional exhaustion may be a predictor of work functioning problems 3 . Furthermore, work engagement (ie, the positive work‐related psychological state of well‐being that is conceptualized by vigor, dedication and absorption 15 ), as the distinct concept that is negatively related to burnout and the predictor of well‐being and work motivation demonstrated in many studies (eg, Christian et al 16 ), was found to be only marginally related to work functioning problems by Abma and colleagues 11,12 . Accordingly, due to the mixed study findings so far it is important to conduct additional research on the predictors of the work functioning of workers.…”
Section: Introductionmentioning
confidence: 94%
“…8,9 Most studies on work functioning problems addressed the measurement properties of instruments relevant for recording work functioning. 2,[10][11][12] To date, only a handful of studies have addressed correlates of work functioning, including personal factors such as self efficacy, 8 health-related factors such as emotional exhaustion, distress, fatigue, depressive, and cognitive syptoms, 3,8,13,14 as well as work-related factors such as work engagement, job content, supervisor social support, and organizational support. 8,13,14 These studies on predictors of work functioning problems of workers so far showed mixed results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventeen studies covering eight instruments screening for psychological distress in HCWs were included in this review [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] ( Table 1 and Supplementary File S3 ). These are the work functioning screener-healthcare (WFS-H) [ 17 ], the Burnout Battery [ 18 ], the Physician well-being index (PWBI) [ 20 , 21 , 22 , 23 ] the Professional quality of Life (ProQOL) [ 16 , 25 , 26 , 27 , 28 , 30 ], the Burnout–thriving index [ 26 ], the single-item burnout [ 19 , 27 , 29 , 32 ] and the Professional fulfilment index (PFI) [ 24 , 31 ]. The sample sizes of the HCWs included in the studies varied from 249 to 7288.…”
Section: Resultsmentioning
confidence: 99%
“…The index test for Hansen’s single-item burnout was judged as ‘low risk’ [ 27 ] and remaining instruments as ‘high risk’. The flow and timing of the WFS-H [ 17 ], Burnout inventory index [ 26 ] and PFI [ 31 ] were judged as ‘low risk’, and other five instruments as ‘unclear’.…”
Section: Resultsmentioning
confidence: 99%